Design and fabrication of an aerator cum oxygen accumulator for live fish transport - Rifat, Sazzad Mahmud; Ashik-E-Rabbani, Muhammad; Basir, Md Samiul; Alam, AKM Nowsad (Journal of the Bangladesh Agricultural University, 2019)
Bangladesh secured the third position in freshwater fish and fisheries product producing country where around 4.134 million metric ton of fish is extracted annually. Fish transporting in traditional method reduces fish freshness and thus causes serious economic loss. Further, for live fish transportation, maintaining water quality is a challenge, with the course of time, oxygen, pH and temperature of water deteriorate. Considering this issue, a study was undertaken to construct simple, low energy consumed aerator-cum-oxygen accumulator for live fish transport. A 12-volt 3-ampere DC motor operated 1100 GPH bilge pump was modified with the venturi principle to construct the aerator. The experiment was conducted to evaluate its performance for live fish transport and compared with the results in a condition of with and without an aerator. 45 (forty-five) numbers of Rohu fish (Labeo Rohita) with an average weight of 378 g were put in a tank of 650 liters for this experiment. After six hours of the test, different parameters were measured in both conditions. With the device, dissolved oxygen and pH level were found as 9.3 mg/l and 7.8 and without the device, dissolved oxygen and pH level were found 6.2 mg/l and 7.1, respectively in six hours of operation. On the other hand, without the device, the dissolved oxygen level decreased from 6.5 mg/l to 2.2 mg/l and pH level increased from 8.30 to 9.70 in six hrs of the test. Besides, by using, the device mortality rate of fishes was zero but without the device, the mortality rate was 11.11%. Water temperature changing was insignificant during the experiment. Results indicate that for reducing losses of fish and increase the income of fisherman, this device might be suitable for live fish transport. <!–StartFragment –> J Bangladesh Agril Univ 17(4): 592–598, 2019